Charge/discharge Profiling of Organic Latent Heat Material Embedded in Polymer Matrix for Heat Energy System - Reza Abdu RAHMAN; Sulistyo SULISTYO; M.S.K.Tony Suryo UTOMO; Ilham FEBRIANSYAH; Ismail ISMAIL (Medžiagotyra)
The operational aspect of a latent thermal energy storage (LTES) system is highly dependent on the performance of its latent heat storage material (LHSM). In this work, performance evaluation of the LHSM is conducted using low-density polyethylene (LDPE) and linear LDPE. As an initial assessment, three different organic LHSMs are used for the evaluation. The thermal assessment indicates that the heat of fusion for the LHSM varies between 142.45 J/g and 198.8 J/g. Thermal decomposition demonstrates that the LHSM is suitable for operating a thermal power system under 100 °C. The addition of polymer clearly influences the charge/discharge rate for each LHSM. For example, it has a positive influence on paraffin wax, which increases the charge rate up to 54.4 %. A positive outcome is also observed for palmitic acid, which has the highest charge rate at around 4.4 °C/min. Interestingly, the charge/discharge rate for stearic acid is decreased by the presence of a polymer. It implies that the melting/solidification rate can be decreased, which may be advantageous for passive thermal systems. In general, the addition of LDPE/LLDPE alters the performance of LHSM. It makes the polymer suitable to be taken as a stabilizer for the LHSM.